International decision making : leadership matters - Hermann, Margaret G. (1998)
Suggests that in the post-Cold War understanding the dynamics of decision making could be key to predicting the behaviour of states. Opines political pressures at home can have a significant impact upon how leaders formulate their policies abroad.